2007
DOI: 10.1038/sj.bmt.1705951
|View full text |Cite
|
Sign up to set email alerts
|

Intensive conditioning regimen of etoposide (VP-16), cyclophosphamide and carmustine (VCB) followed by autologous hematopoietic stem cell transplantation for relapsed and refractory Hodgkin's lymphoma

Abstract: Several high-dose therapy regimens are used for autologous hematopoietic stem cell transplantation (auto-HSCT) for relapsed and refractory Hodgkin's lymphoma (HL) with variable disease response. An intensified regimen of etoposide (VP-16) 2400 mg/m 2 , cyclophosphamide 7200 mg/m 2 and carmustine (BCNU) 600 mg/ m 2 (VCB) pre-auto-HSCT was developed to overcome disease recurrence. A total of 43 relapsed and refractory HL patients underwent auto-HSCT between January 1992 and December 2004. At day 100 there were 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…High-dose chemotherapy followed by hematopoietic stem cell transplantation is associated with an inherent risk of pneumonitis, even in the absence of thoracic RT [29, 30]. However, when peri-transplant RT is administered, the risk of pneumonitis increases, as shown in several studies [14, 3133].…”
Section: Discussionmentioning
confidence: 99%
“…High-dose chemotherapy followed by hematopoietic stem cell transplantation is associated with an inherent risk of pneumonitis, even in the absence of thoracic RT [29, 30]. However, when peri-transplant RT is administered, the risk of pneumonitis increases, as shown in several studies [14, 3133].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies showed that higher doses of BCNU increase risk of pulmonary toxicity as high as 35% [56,57]. In an effort to reduce pulmonary toxicity, Arai et al (2010) conducted a phase I/II study of conditioning regimen using gemcitabine along with vinorelbine (gemcitabine maximum tolerated dose 1250 mg/m2) [58].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to improve on FFP in AHCT have included further intensification of salvage therapy before transplant [2-7], or intensification of the transplant conditioning regimen itself either with high dose sequential therapy [8-9] or with augmented carmustine (BCNU)-based regimens [10-16]. With increasing doses of BCNU from 300 mg/m 2 to 600 mg/m 2 , however, the incidence of pulmonary toxicity increases to 35% and higher [17-20]. When oral lomustine (CCNU) was substituted for BCNU in the conditioning, the interstitial pneumonitis incidence was as high as 63% [19].…”
Section: Introductionmentioning
confidence: 99%